16S Ribosomal RNA Gene PCR and Sequencing for Pediatric Infection Diagnosis, United States, 2020–2023 - Guyu Li; Christopher A. Reis; Rebecca M. Kruc; Ziyuan Zhang; Nicholas T. Streck; Elizabeth H. Ristagno; Jay Mandrekar; Matthew J. Wolf; James T. Gaensbauer; Robin Patel (Emerging Infectious Diseases)
Gene PCR and sequencing using 16S ribosomal RNA (rRNA) can help diagnose challenging bacterial infections. Data on the optimal clinical settings for this type of testing are limited. We performed a retrospective study at Mayo Clinic, Rochester, Minnesota, USA, with typically sterile specimens from children that underwent 16S rRNA PCR testing during September 2020–December 2023. Of 162 tests performed on 124 patients, 20% were positive; 58% of positive samples were from culture-negative specimens. Fluid specimens were >3 times as likely to test positive as tissue specimens (odds ratio 3.07 [95% CI 1.32–7.11]; p = 0.007), and pleural fluid demonstrated the highest positivity rate (50%). Of 33 positive results, 4 (12%) specimens qualified for reporting to the state health department for communicable diseases. Those single-laboratory findings demonstrate that the highest positivity rate of 16S rRNA PCR and sequencing is pleural fluid, although many specimen types tested positive.